2016
DOI: 10.1021/acs.energyfuels.6b00174
|View full text |Cite
|
Sign up to set email alerts
|

Online Size and Element Analysis of Aerosol Particles Released from Thermal Treatment of Wood Samples Impregnated with Different Salts

Abstract: Thus far, the elemental characterization of particles in energy conversion process gases and emissions has conventionally either been performed offline or information on the particle size has not been available. Such processes include combustion in engines or thermal treatments of renewable and fossil fuels for heat and power generation. One established physical aerosol measurement instrument is the scanning mobility particle sizer (SMPS), providing size distribution and concentration of gas-borne particles on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The Agricultural Burning source was identified by semiconfident attributions of PO 4 3– , K, Zn, Mo, and low confidence attributions of many crustal species (Figure D, Table S4). Potassium is commonly associated with biomass burning emissions, , and biomass burning events are also known to be important mechanisms of P redistribution . The crustal elements associated with this factor, which likely represent coemitted dust, are similar to that of Colorado Alluvium , with high Ca and low Ti, Al, and Fe (Figure , Table S4), and can be explained by agricultural biomass burning on farmed Colorado alluvial soils in the Salton Sea basin.…”
Section: Resultsmentioning
confidence: 97%
“…The Agricultural Burning source was identified by semiconfident attributions of PO 4 3– , K, Zn, Mo, and low confidence attributions of many crustal species (Figure D, Table S4). Potassium is commonly associated with biomass burning emissions, , and biomass burning events are also known to be important mechanisms of P redistribution . The crustal elements associated with this factor, which likely represent coemitted dust, are similar to that of Colorado Alluvium , with high Ca and low Ti, Al, and Fe (Figure , Table S4), and can be explained by agricultural biomass burning on farmed Colorado alluvial soils in the Salton Sea basin.…”
Section: Resultsmentioning
confidence: 97%
“…Figures of merit given by Hess et al 2 0 show that the performance of the developed SMPS-ICPMS instrumentation is comparable to that of the separate state-of-the-art systems. This study is complementary to the previous publications 19 20 21 and gives a laboratory practice describing how this setup can be used. Example applications on aerosols from two different sources are shortly described, to show the versatility of the coupled system.…”
Section: Introductionmentioning
confidence: 92%
“…A Rotating Disk Diluter (RDD) is used as the introduction interface. The development of this hyphenated technique and three application studies can be found in the literature 19 20 21 . Figures of merit given by Hess et al 2 0 show that the performance of the developed SMPS-ICPMS instrumentation is comparable to that of the separate state-of-the-art systems.…”
Section: Introductionmentioning
confidence: 99%
“…Figures of merit given by Hess et al 20 show that the performance of the developed SMPS-ICPMS instrumentation is comparable to that of the separate state-of-the-art systems. This study is complementary to the previous publications 19,20,21 and gives a laboratory practice describing how this setup can be used. Example applications on aerosols from two different sources are shortly described, to show the versatility of the coupled system.…”
Section: Introductionmentioning
confidence: 93%
“…A Rotating Disk Diluter (RDD) is used as the introduction interface. The development of this hyphenated technique and three application studies can be found in the literature 19,20,21 . Figures of merit given by Hess et al 20 show that the performance of the developed SMPS-ICPMS instrumentation is comparable to that of the separate state-of-the-art systems.…”
Section: Introductionmentioning
confidence: 99%